DIGITAL TRANSFORMATION OF ARABIC WRITING INSTRUCTION THROUGH INTERACTIVE MULTIMEDIA INTEGRATION - Indy Aslihah; Umar Faruq; Yuyun Zunairoh; Ahmad Umar Faruq; Aliy Rahman (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2026)
This study aims to develop and examine the effectiveness of Smart Kitabah media based on I-Spring Suite 11. Employing the ADDIE model combined with a quasi-experimental one-group pretest-posttest design, this research involved madrasah students selected via purposive sampling. Data collection used a validated test instrument (Cronbach’s Alpha = 0.803), expert validation sheets, teacher practicality forms, and student questionnaires. The findings revealed that the media achieved high validity from material (97%) and media (95%) experts. In classroom implementation, teachers rated it highly practical for usability (96%), content alignment (98%), and attractiveness (97%). Statistically, students' writing proficiency scores increased from a pretest mean of 42.23% to a posttest mean of 42.23% to a posttest average of 80.62%. Paired sample t-test showed a significant difference (p < 0.05) with a high-category N-Gain score, complemented by an 86.26% excellent student response. These results justify Mayer’s Cognitive Theory of Multimedia Learning and CALL framework in reducing cognitive load. This study concludes that Smart Kitabah is highly effective and applicable for modernizing Arabic language pedagogy